2020
DOI: 10.1155/2020/6971702
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Radial Distribution Laws of Rock Mass Damage Factors under Decoupled Charge Blasting

Abstract: In this paper, the radial distribution laws of damage factors under decoupled charge blasting are studied for the optimization design of blasting parameters. Through defining the critical radial decoupling coefficient, the damage zone around the borehole is partitioned and the characteristics are described. Based on the damage factor defined by Taylor’s effective elastic modulus, the formulas of the radial distribution laws of damage factors are derived by the attenuation law of stress wave and the theory of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Gong Jiu et al [12] found that compared to air uncoupled charges, water uncoupled charges have a higher utilization rate of explosion energy and are more conducive to improving the blasting effect. Pan Qiang et al [13] found that the damage factor of uncoupled charge blasting decays in a power function, and the decay rate increases with the increase of uncoupled coefficient when K<K0. Zhang Liwei et al [14] found that as the spacing between holes increases, the degree of damage between the connecting lines of the blast holes decreases, and the damage area between the connecting lines changes from continuous to discontinuous.…”
Section: Introductionmentioning
confidence: 99%
“…Gong Jiu et al [12] found that compared to air uncoupled charges, water uncoupled charges have a higher utilization rate of explosion energy and are more conducive to improving the blasting effect. Pan Qiang et al [13] found that the damage factor of uncoupled charge blasting decays in a power function, and the decay rate increases with the increase of uncoupled coefficient when K<K0. Zhang Liwei et al [14] found that as the spacing between holes increases, the degree of damage between the connecting lines of the blast holes decreases, and the damage area between the connecting lines changes from continuous to discontinuous.…”
Section: Introductionmentioning
confidence: 99%